Criminal-legal Mechanism of Counteraction of Insider Activity in the Stock Market - MALYSHENKO, K.A.; MALYSHENKO, V.A.; BEKIROVA, E.S.; BEKIROV, S.N.; ARKHIPOVA, S.V.; ANASHKINA, M.V. (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019, 2019)
Protecting the rights of stock market participants in the modern world is an important aspect of its functioning, ensuring the security of investments of participants and their property status. The misuse of insider information with the aim of obtaining certain benefits, and market manipulation are some of the most ambitious crimes that violate the rights of a wide range of people, and a direct threat to their material well-being. Insider trading involves trading transactions with securities, which is carried out by private individuals, holding information about the Issuer of the financial asset. In this work, we use methods of legal statistics that allow us to obtain quantitative data on the application of liability for violations of anti-insider Russian legislation. In addition, a comparative legal method is used to comparatively characterize measures to combat insider activity in the world. The purpose of the research is to identify the shortcomings of the modern criminal law mechanism for countering insider activity in the Russian securities market and develop measures to improve its effectiveness. The criminal law regulation of insider information in the world and domestic experience are analyzed. As a result of the study, a number of shortcomings inherent in this mechanism were identified. Thus, the study of foreign practice has shown that the existing measures in Russia to combat insiders in the securities market are not effective. This is due to many factors, the main of which are the imperfection of the legal framework, the lack of practical application of criminal penalties, their low effectiveness, the lack of specific penalties, etc. The article highlights the problems of administrative and criminal liability for market manipulation and illegal use of insider information. The article analyzes the criminal law regulation of mitigating liability for insider information in the world and domestic experience.Based on the analysis and comparison of Russian and international practices in the fight against insiders, conclusions are drawn about the need to adjust the domestic monitoring mechanism and improve criminal law methods to ensure its functioning.The article actualizes the problems of administrative and criminal liability for the manipulation of the market and the misuse of insider information.